Virulence diversity in Puccinia striiformis f.sp. tritici causing yellow rust on wheat (Triticum aestivum) in India - O.P. GANGWAR, M. PRASHAR, S.C. BHARDWAJ*, S.K. JAIN (Indian Phytopathology, 2015)
Yellow (or stripe) rust caused by Puccinia striiformis f. sp. tritici (Pst) is an important foliar disease on wheat in the North-western Plains Zone (NWPZ), Northern hills zone, and Southern hills zone of India. The pathogen population was analyzed for phenotypic dynamics, diversity and virulence evolution on temporal and spatial bases. A total of eight pathotypes were identified from 2579, yellow rust samples analyzed during 2004-2011 from nine states of India. The Pst population reveals high virulence with low diversity. The population was dominated primarily by three pathotypes, 78S84 and 46S119 in Northern India and 38S102 (I) in the Nilgiri Hills. Based on avirulence/virulence structure, our population of yellow rust is different to that of Western Asia and South Africa and appears to have evolved locally. Relative Shannon’s index (HSR) exhibits insignificant differences in diversity (richness) and evenness of the pathotypes over the years. The frequency of 78S84 remained all time high on yearly basis except crop season 2004-05. In Nilgiri Hills (Tamil Nadu), pathotype, 38S102, revealed consistently decreased frequency over the year and was not detected in 2009-10 crop season. Pathotype, 78S84, was predominant in Jammu and Kashmir, Himachal Pradesh, Punjab and Western Uttar Pradesh, whereas, 46S119 in Haryana, Uttarakhand, Rajasthan and Delhi. New virulent types have mainly evolved by mutation for virulence to host resistance, and subsequent dominance of pathotypes has been influenced by parasitic fitness and opportunity to be selected through large-scale cultivated varieties with matching resistance genes. Pathotype analyses revealed that wheat yellow rust population of India is avirulent to Yr5, Yr10, Yr11, Yr12, Yr13, Yr14, Yr15, Yr24, Yr26, YrSp and YrSk. Phenotypic spatial and temporal dynamics and diversity in pathogen population, virulence evolution is of prime focus.